Green synthesized CaO decorated ternary CaO/g-C3N4/PVA nanocomposite modified glassy carbon electrode for enhanced electrochemical detection of caffeic acid - Karthika, Annamalai; Sudhakar, C.; Karuppasamy, Periyakaruppan; Tamilselvi, Baluchamy; Meena, Subramaniam; Anantharaju, Kurupalya Shivram; Tan, K. B.; Murthy, H. C. Ananda (Nature Research, 2024)
A highly selective, sensitive caffeic acid (CA) detection based on calcium oxide nanoparticles (CaO NPs) derived from extract of Moringa oleifera leaves decorated graphitic carbon nitride covalently grafted poly vinyl alcohol (CaO/g-C3N4/PVA) nanocomposite modified glassy carbon electrode (GCE) was studied. A facile sonochemical method was adapted to synthesis nanomaterials and characterized by HR-TEM (High resolution transmission electron microscopy), FT-IR (Fourier transform infrared spectroscopy), XRD (X-ray diffraction), FE-SEM (Field emission scanning electron microscopy), EDX (Energy dispersive X-ray analysis), Mapping and BET (Brunauer-Emmett-Teller) analysis, and electrochemical techniques. The nanocomposite modified GCE exhibited an excellent catalytic performance to the oxidation of CA under optimized conditions owing to better electron transfer efficiency, conductivity and high surface area of the electrode material. The present electrochemical sensor showed high selectivity towards the determination of 10 µM CA in the presence of 100-fold higher concentrations of interferents. The modified CA sensor exhibited a wide sensing linear range from 0.01 µM to 70 µM and the detection limit (LOD) was found to be 0.0024 µM (S/N = 3) in 0.1 M phosphate buffer saline (PBS) as a supporting electrolyte at pH 7.0. The fabricated CA sensor provides an excellent stability, reproducibility and selectivity for the determination of CA. The modified CA sensor was applied to real blood plasma samples and obtained good recovery (97.6-100.1%) results. © The Author(s) 2024.